Sg. Serai water characterization and coagulation study / Safrina Mohd Aziz - Mohd Aziz, Safrina (2010)
The Sg. Serai Water Treatment Plant is a partial water treatment which only treats raw water with turbidity less than 5 NTU. Recently, the raw water turbidity increased to 6-8 NTU due to several landslides at the upstream of the intake. The low turbidity water in Sg Serai is hard to coagulate due to low concentration of particles. Study on different coagulants and optimization of the coagulant dosage on Sg. Serai raw water essential to ensure the WTP can be operated to produce treated water that comply with the Malaysian Drinking Water Quality Standard and Concession Agreement. Nine water quality parameters were conducted to characterize the Sg Serai raw water prior to coagulation study. Forty- one jar tests were conducted for coagulation and flocculation study to determine optimum dosages and pH for coagulation process. In addition, the jar tests were conducted to evaluate the performance of selected aluminium based coagulant with and without pre-treatment. Furthermore, filtrations test conducted to evaluate the effectiveness of the combined coagulation and filtration in treating raw water. The characterization of raw water showed that TOC and color are very low thus may not dominant in affecting optimum coagulation dosage. The pH and alkalinity is also low which 6.23 mg/L and 3.4 mg/L respectively, demanding the pre-treatment such as pH correction and water softening. The low turbidity in raw water containing small colloid particles (0.5658 µm) also raise problem in optimization of the coagulation process due to less collision between particles. The zeta potential is -28mV showed high negative charge on colloids that much need to be reduced to the range of 0 mV to -10mV for optimum coagulation process. The study discovered that the optimum pH for coagulation process using alum without pre- treatment is pH 4.3 to 6.38 and pH 5.23 to 7.71 with pre-treatment. While the optimum pH coagulation for PAC without pre- treatment is pH 4.54 to 7.24 and pH 5.06 to 6.52 with pre- treatment. The optimum dosage for alum for was at 15 mg/L with 96.5 % turbidity removal. The optimum dosage of PAC was smaller compared to Alum at 5 mg/L PAC with 64.1% turbidity removal. Thus, the result showed that the alum is the most effective in removing turbidity in Sg. Serai raw water compared to PAC. The coagulation with pre- treatment is effective with pre- treatment for both alum and PAC. Alum is the most effective with pre- treatment with 98.6% turbidity removal. pH adjustment is important for optimization of alum coagulant due to its smaller optimum pH range. The filtration had removed 21.7% and 32.7% turbidity of settled water when alum and PAC was used as coagulant in clarification process respectively. Thus, the combination of coagulation, flocculation, sedimentation and filtration were effective and efficient to remove turbidity of Sg. Serai water with pre- treatment in using alum and PAC.